Бруски: роман в 4 книгах - Панферов Федор Иванович (Библиотека "Огонек", 1986)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 17777 / Цена: 2.90 / Сис.шифр: Р2 / Авт.знак: П 16 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6